Acute Kidney Injury in Critically Ill Patients - Setyawan, Yuswanto (Universitas Sam Ratulangi, 2021)
Abstrak: Gagal ginjal akut (GGA) sering ditemukan dalam praktek klinik namun diagnosisnya dapat tertunda oleh karena keterbatasan alat diagnostik. Dewasa ini, kriteria diagnostik RIFLE, AKIN, dan KDIGO untuk menilai adanya GGA dan keparahannya dianggap tidak cukup untuk menggambarkan kompleksitas sindrom GGA. Proteinuria dan mikroalbuminuria yang merupa-kan marker klasik progresi cedera ginjal kronik, telah dipergunakan dan divalidasi untuk progresi GGA ke CKD. Kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), dan urinary cystatin C dapat berperan dalam memrediksi pemulihan ginjal. Indikasi biopsi ginjal pada pasien kritis ialah gangguan ginjal yang tidak jelas atau progresi CKD dengan hematuria glomerulus dan proteinuria lebih dari 1 gram per hari, manifestasi ginjal dari penyakit sistemik yang mengancam nyawa, kecurigaan penolakan akut atau kronik dari ginjal transplan. Mempertahankan hemodinamik yang adekuat seharusnya bermanfaat dalam pence-gahan onset atau perburukan GGA, namun kelebihan cairan harus dihindari. Sampau saat ini penentuan saat inisiasi acute renal replacement therapy (ARRT) masih kontroversial, demikian pula nilai ambang spesifik untuk memulainya belum sepenuhnya disepakati. Kata kunci: gagal ginjal akut; penyakit kritis' laju filtrasi glomerulus (LFG)Â Â Abstract: Acute kidney injury (AKI) is a common problem in clinical practice, but its diagnosis could be delayed due to the inherent limitation of current diagnostic tools. Current practice suggests that RIFLE, AKIN, and KDIGO diagnostic criteria used to assess the presence of AKI and its severity are insufficient to illustrate the complexity of the AKI syndrome. Proteinuria and micro-albuminuria, classical markers of chronic kidney disease (CKD) progression, have been used and validated for the progression of AKI to CKD. Kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), and urinary cystatin C could play a role in prediction of renal recovery. Indication of renal biopsy in critically ill patients are unexplained renal impairment or progression of CKD with both glomerular hematuria and proteinuria more than 1 gr per day, renal manifestations of life threathening systemic disease, suspected acute or chronic rejection of a transplanted kidney. The maintenance of adequate hemodynamics should be beneficial in preventing the onset or the worsening of AKI, but fluid overload should be avoided. Timing of acute renal replacement therapy (ARRT) initiation is still controversial, moreover, specific thresholds for starting are still unclear.Keywords: acute kidney injury (AKI); critically ill; glomerular filtration rate (GFR)